Vibration Characteristics of Roundabout Swing of HAWT Wind Wheel - Jian-long Ma; Pei-lin Li; Jian-wen Wang; Liu Yang; Yan-qi Zhang (Shock and Vibration)
Modal testing was used to show that the roundabout swing was a natural vibration mode of the wind wheel of a horizontal-axis wind turbine (HAWT). During the vibration, the blade root was simultaneously subjected to bending and rotary shear stresses. A method for indirect testing and determination of the dynamic frequencies of the typical vibrations of the wind wheel was developed, based on the frequency-holding characteristic of each subsignal during the transmission of the multiple mixed-vibration signals. The developed method enabled simple and accurate acquisition of the dynamic frequencies without destruction of the flow and structural fields. The dynamic vibration stress of the roundabout swing was found to be significantly stronger than those of the first- and second-order flexural vibrations of the blades. By a combination of numerical simulations and tests, it was determined that the pneumatic circumferential force was the primary determinant of the roundabout swing vibration frequencies, the relationship being quadratic. The roundabout swing vibration potentially offers new explanations and analytical pathways regarding the behavior of horizontal-axis wind turbines, which have been found to be frequently involved in fatigue-damage accidents within periods shorter than their design lives.